6-Gingerol anti-inflammatory and antioxidant properties protect against heart and liver dysfunction in rats with sepsis - Helia Keivanpour; Reihaneh Zamzam; Mojtaba Mojtahedzadeh; Mohammad-Reza Delnavazi; Amin Sharifan; Omid Sabzevari (Elsevier, 2024)
Objective: To investigate the effect of 6-gingerol, active component of Zingiber officinale (Shēngjiāng), on sepsis-induced inflammation, oxidative injury, and organ damage in vivo. Methods: 6-gingerol was extracted from ginger, and its identity was confirmed with 1H NMR, 13C NMR, and TLC. Sepsis was induced via cecal ligation and puncture (CLP) in all groups except for sham. Thirty male Wistar rats were randomly divided into sham, CLP alone, 6-gingerol, ginger extract, hydrocortisone, and solvent. Treatments were administered intraperitoneally with a dose of 25 mg/kg. Biomarkers for inflammation, oxidative injury, and organ damage were assessed. Furthermore, heart and liver organs were stained with hematoxylin-eosin to determine the extent of sepsis-induced organ damage. Results: 6-gingerol with 98.9 % purity was extracted. Compared with CLP-alone, biomarker analyses indicated that 6-gingerol significantly attenuated sepsis-induced inflammation by decreasing the levels of tumor necrosis factor-α, interleukin-6, and nuclear factor-κB. Furthermore, this bioactive constituent markedly reduced oxidative stress during sepsis by replenishing the levels of glutathione, increasing catalase, and decreasing malondialdehyde and superoxide. Moreover, organ damage assays showed that 6-gingerol substantially reduced the levels of cardiac troponin I, alanine aminotransaminase, aspartate aminotransferase, and lactate dehydrogenase, showing protective effects against cardiac and hepatic dysfunction. Similarly, rats treated with 6-gingerol had normal hepatic lobules, fewer Kupffer cells in minor regions of the liver, and lower necrosis and apoptosis in the myocardium. Discussion: 6-gingerol protects both heart and liver organs through its anti-inflammatory and antioxidant effects in septic rats.